Development of algorithm of implementation of operations of passing to information - Бойченко, О.В. (Proceedings of National Aviation University, 2010)
Wide introduction of the informatively telecommunication systems in all of directions of vital functions of society needs introduction of scientific researches in relation to the improvement of methods of development of algorithm of conducting the operations of transferring the information. The most known methods of conducting the operations of transferring the information determine priority of cyclic transferring of data to a processor, it provides the optimum of amount of transferring the information with the observance of requirements of authenticity and quality of transferrable information in the multiprocessor computer system.